A Postmodern Thanatic Triad: Crisis, Pornography and Renaissance of Death - Zakowicz, Ilona (Journal of Education Culture and Society, 2020)
In every age we can find a different attitude of man towards the end of life, instanced in varied stances and imaginations regarding death. In postmodernism, which makes a broader context for this work, it is impossible to present one unified image of death, because the attitude of contemporary men towards death and the visual forms of it are greatly varied. The subject of my analysis is a presentation of death shown in three occurrences the crisis, the pornography and the renaissance of death which combine to form the postmodern thanatic triad.